2022
DOI: 10.1111/dth.15845
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of baricitinib in patients with refractory alopecia areata

Abstract: Alopecia areata (AA) is an autoimmune disorder characterized by nonscarring hair loss. 1 Numerous treatment options are available for AA. 2,3 However, it is often challenging and unsatisfactory for refractory AA treatment. Recently, Janus kinase inhibitors (JAKis) have shown promising results in treating AA. 4 For example, baricitinib has shown good clinical efficacy in two phase 3 trials involving patients with severe AA. 5 Here we present a case series of 11 patients with refractory AA treated with baricitin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Recently, Wang et al. [ 21 ], reported a case series of 11 patients with AA, including two participants under the age of 18 years, treated with baricitinib for 20 weeks. Complete remission was achieved in two patients, while three patients, including one of the adolescents, did not respond to therapy at all.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Wang et al. [ 21 ], reported a case series of 11 patients with AA, including two participants under the age of 18 years, treated with baricitinib for 20 weeks. Complete remission was achieved in two patients, while three patients, including one of the adolescents, did not respond to therapy at all.…”
Section: Discussionmentioning
confidence: 99%
“…4 In a recent study, 11 patients with refractory AA were treated with baricitinib (JAK1/2 inhibitor), and 27% of patients achieved SALT 50 with twice-daily oral baricitinib (2 mg dose). 5 These successful attempts suggest that JAK inhibitors can be used in refractory AA, and have achieved good results.…”
Section: Effective Treatment Of Refractory Alopecia Areata In Pediatr...mentioning
confidence: 99%
“…Other researchers also observed various shrinking of the alopecia area after weeks 12 and 24 in both adult 17,18 and pediatric patients. 19 However, the SALT value at week 4 was not significantly inferior to baseline, indicating that a minimum treatment duration of more…”
Section: Discussionmentioning
confidence: 76%
“…Besides, in our study, the hair restoration level observed at week 24 was superior to that of week 12 with a statistical difference. Other researchers also observed various shrinking of the alopecia area after weeks 12 and 24 in both adult 17,18 and pediatric patients 19 . However, the SALT value at week 4 was not significantly inferior to baseline, indicating that a minimum treatment duration of more than 12 weeks was required to determine whether a patient had a response to baricitinib.…”
Section: Discussionmentioning
confidence: 88%